PENGARUH METODE MIND MAPPING TERHADAP HASIL BELAJAR FISIKA SISWA PADA KONSEP RANGKAIAN LISTRIK DINAMIS - Anjarsari (CV. ADIBA AISHA AMIRA, 2024)
This study aims to determine the effect of mind mapping method on physics learning outcomes. This research was conducted at Al-Masthuriyah Senior High School (SMA), Sukabumi Regency on the concept of dynamic electricity. This research was conducted for five meetings, starting from September 4-25, 2023. The research method used was quasi experiment with purposive sampling technique. The instruments used were test instruments in the form of multiple choice questions as many as 26 items and non-test instruments in the form of a questionnaire of student perceptions of mind mapping in physics learning. The data from the instrument results were analyzed by statistical tests in the form of t-tests, while the data from the questionnaire non-test instruments were analyzed qualitatively descriptively. The results showed that there was an influence on physics learning outcomes by using mind mapping. This conclusion is based on the results of hypothesis testing using t-test. Based on the hypothesis testing, the t-count value is 2.07, and the t-table value at the 5% significance level is 2.008. Thus, it can be seen that t-count > t-table, so the null hypothesis is rejected. In addition to the t-test, the effect of mind mapping can also be seen from the average value of the pretest, which is 26.51 which increases in the average value of the posttest, which is 71.37.